Type Ibn Supernovae Show Photometric Homogeneity and Spectral Diversity at Maximum Light - Hosseinzadeh, Griffin; Arcavi, Iair; Valenti, Stefano; McCully, Curtis; Howell, D. Andrew; Johansson, Joel; Sollerman, Jesper; Pastorello, Andrea; Benetti, Stefano; Cao, Yi; Cenko, S. Bradley; Clubb, Kelsey I.; et al. (The Astrophysical journal, 2017)
Type Ibn supernovae (SNe) are a small yet intriguing class of explosions whose spectra are characterized by low-velocity helium emission lines with little to no evidence for hydrogen. The prevailing theory has been that these are the core-collapse explosions of very massive stars embedded in helium-rich circumstellar material (CSM). We report optical observations of six new SNe Ibn: PTF11rfh, PTF12ldy, iPTF14aki, iPTF15ul, SN 2015G, and iPTF15akq. This brings the sample size of such objects in the literature to 22. We also report new data, including a near-infrared spectrum, on the Type Ibn SN 2015U. In order to characterize the class as a whole, we analyze the photometric and spectroscopic properties of the full Type Ibn sample. We find that, despite the expectation that CSM interaction would generate a heterogeneous set of light curves, as seen in SNe IIn, most Type Ibn light curves are quite similar in shape, declining at rates around 0.1 mag day−1 during the first month after maximum light, with a few significant exceptions. Early spectra of SNe Ibn come in at least two varieties, one that shows narrow P Cygni lines and another dominated by broader emission lines, both around maximum light, which may be an indication of differences in the state of the progenitor system at the time of explosion. Alternatively, the spectral diversity could arise from viewing-angle effects or merely from a lack of early spectroscopic coverage. Together, the relative light curve homogeneity and narrow spectral features suggest that the CSM consists of a spatially confined shell of helium surrounded by a less dense extended wind.